2007
DOI: 10.1111/j.1440-1754.2007.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating inspired oxygen concentration delivered by nasal prongs in children with bronchiolitis

Abstract: In this study, it was not possible to estimate FiO(2) reliably from nasal oxygen flow rates in children with bronchiolitis. Nasal prong oxygen flow rates should be used with caution when assessing the severity of bronchiolitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…These results help to explain previous observations of high variability in FiO 2 delivered through nasal cannulas to neonates and infants, even at fixed nasal cannula flow rates [ 8 , 9 , 11 , 12 ]. Variability in FiO 2 was determined by variation in two breathing parameters: tidal volume and inhalation time.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results help to explain previous observations of high variability in FiO 2 delivered through nasal cannulas to neonates and infants, even at fixed nasal cannula flow rates [ 8 , 9 , 11 , 12 ]. Variability in FiO 2 was determined by variation in two breathing parameters: tidal volume and inhalation time.…”
Section: Discussionsupporting
confidence: 80%
“…Measurement of the FiO 2 delivered through nasal cannulas to patients is challenging because of the invasiveness of catheters required to sample gas from the hypopharynx [ 7 ], or the need to infer FiO 2 based on non-invasive surrogate measures if catheters are not used [ 8 , 9 ]. Moreover, simultaneous time-resolved measurements of inhaled oxygen concentration and breathing waveforms are difficult to obtain in vivo in neonates and infants, so previous studies have relied on assumed, rather than measured, breathing parameters when evaluating their influence on FiO 2 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[106][107][108] Supplemental oxygen provided for infants not requiring additional respiratory support is best initiated with nasal prongs, although exact measurement of fraction of inspired oxygen is unreliable with this method. 109 Pulse oximetry is a convenient method to assess the percentage of hemoglobin bound by oxygen in children. Pulse oximetry has been erroneously used in bronchiolitis as a proxy for respiratory distress.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…Supplemental oxygen delivered via headbox or nasal catheters is the mainstay of therapy for infants with hypoxaemia. However, despite the fact that the oxygen flow rate required to maintain satisfactory oxygenation is used as a proxy for severity, it has been recently demonstrated that it is not possible to reliably estimate the FiO 2 reliably from nasal oxygen flow rates in infants with bronchiolitis 30 . There are no universally accepted thresholds for introducing or weaning supplemental oxygen.…”
Section: Pharmacological Treatment At Presentationmentioning
confidence: 99%